Complement System Proteins in the Human Aqueous Humor and Their Association with Primary Open-Angle Glaucoma - Vashishtha, Ayushi; Maina, Sharon W.; Altman, Jeremy; Jones, Garrett; Lee, Tae Jin; Bollinger, Kathryn E.; Ulrich, Lane; Töteberg-Harms, Marc; Estes, Amy J.; Zhi, Wenbo; Sharma, Shruti; Sharma, Ashok (Journal of personalized medicine, 2023)
This study discovers the complement protein profile in the aqueous humor (AH) of human subjects and investigates its association with primary open-angle glaucoma (POAG) pathogenesis. Among the 32 complement proteins identified, 22 were highly abundant and detected in more than 50% of AH samples. The most predominant active complement proteins in the AH are C3, C4B, C4A, CFB, CFD, and C9. Additionally, the most prevalent complement regulators and receptors include CLU, SERPING1, F2, CFH, CFI, and VTN. Significant alterations in complement proteins were observed in individuals with POAG compared to those with cataracts. Specifically, complement protein F2 was upregulated, while C8G, C6, and CFH were downregulated in POAG samples. Stratification of the samples by race and sex revealed distinct alterations of complement proteins in patients with POAG. In the African American cohort, five complement proteins (C4A, C4B, F2, C7, and C3) were upregulated in POAG compared to cataract patients. In the Caucasian cohort, eight complement proteins (C3, SERPING1, CFI, CLU, CFHR1, C8G, C6, and CFH) were downregulated in the POAG samples compared to the cataract samples. Within the male cohort, three complement proteins (CLU, C6, and CFH) were downregulated in POAG patients compared to those with cataracts. Whereas, within the female cohort, two complement proteins (C4B and F2) were upregulated and one (C8G) downregulated in the POAG samples when compared to cataracts. Discerning these changes in the AH complement protein profile will assist in the development of tailored therapies to modulate the complement system for managing ocular disorders. These insights may also lead to novel biomarkers for diagnosing and monitoring disease progression.